Characterising successful and unsuccessful aerial manoeuvres in professional surfing competitions - Forsyth, J. R.; Riddiford-Harland, D. L.; Steele, J. R, (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Although aerials are an effective way for a competitive surfer to increase their score during surfing competitions, less than half of aerial attempts are landed successfully during competition. This study aimed to identify which characteristics of performing an aerial during competition were associated with either a successful or unsuccessful landing. Video images of 121 aerials performed during the finals series of the 2015 World Championship Tour season were qualitatively analysed. The Frontside Air Reverse was found to be the most commonly performed aerial, with critical features of landing, particularly features that improved a surfer's balanced landing position, significantly associated with successful aerials. These results provide evidence upon which coaches can modify a surfer's technique to encourage higher successful aerial completion rates.